PROFITABILITAS, STRUKTUR MODAL, DAN FAKTOR LAINNYA YANG MEMPENGARUHI NILAI PERUSAHAAN NON KEUANGAN - Gamaliel Arta Prima Sinurat; Fung Njit Tjhai (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to provide empirical evidence regarding the influence of profitability, capital structure, managerial ownership, company growth, leverage, liquidity, firm size, and dividend policy to firm value. The population used in this research is non-financial companies that are consistently listed on the Indonesia Stock Exchange (IDX) during the period of 2017-2019. There are 54 companies that have met the criteria and resulting 162 data for this research. The data then was analyzed using the multiple regression. The result of this research indicate that profitabilty, capital structure, company growth, leverage, and firm size have an effect on firm value. Meanwhile, other variable such as managerial ownership, liquidity, and dividend policy have no effect on firm value